2012
DOI: 10.7314/apjcp.2012.13.11.5525
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Breast Cancer Mortality Rate Compared to the General Female Population of Iran

Abstract: Introduction: Breast cancer is the most common cancer in women. Improvements of early diagnosis modalities have led to longer survival rates. This study aimed to determine the 5, 10 and 15 year mortality rates of breast cancer patients compared to the normal female population. Materials and Methods: The follow up data of a cohort of 615 breast cancer patients referred to Iranian Breast Cancer Research Center (BCRC) from 1986 to 1996 was considered as reference breast cancer dataset. The dataset was divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 13 publications
2
29
1
Order By: Relevance
“…The knowledge about periods of risks and common site of disease relapse could be used as a guide for focusing on clinical history and physical exams during the follow up visits and screening tests which provide the most information. Mean age of diagnosis in our study was 47.9±9.6 which was lower comparing to study of Su et al (2010) and Kadivar et al (2012) with a mean age of 53±10.4 years old at the time of diagnosis but Bennis et al (2012) similar to Tunisian study in which the mean age of diagnosis was reported 46.8±12 and Haghighat et al (2012) was higher comparing to Iranian study with a mean age of 45.9±10.5. In our patients 9% were under 35 years old and 63.5% were over 50 years old,similar to other Iranian study, patients under 35 years old were 12% and patients over 50 years old were 42% (Kadivar et al, 2012), with regard to study of Webster et al (2008) patients under 35 years old were 6.2% and patients over 50 years old were 37.8% (Webster et al, 2008), our patients had breast cancer at a younger age,possibily due to ethnic and genetic differences.…”
Section: Discussioncontrasting
confidence: 77%
“…The knowledge about periods of risks and common site of disease relapse could be used as a guide for focusing on clinical history and physical exams during the follow up visits and screening tests which provide the most information. Mean age of diagnosis in our study was 47.9±9.6 which was lower comparing to study of Su et al (2010) and Kadivar et al (2012) with a mean age of 53±10.4 years old at the time of diagnosis but Bennis et al (2012) similar to Tunisian study in which the mean age of diagnosis was reported 46.8±12 and Haghighat et al (2012) was higher comparing to Iranian study with a mean age of 45.9±10.5. In our patients 9% were under 35 years old and 63.5% were over 50 years old,similar to other Iranian study, patients under 35 years old were 12% and patients over 50 years old were 42% (Kadivar et al, 2012), with regard to study of Webster et al (2008) patients under 35 years old were 6.2% and patients over 50 years old were 37.8% (Webster et al, 2008), our patients had breast cancer at a younger age,possibily due to ethnic and genetic differences.…”
Section: Discussioncontrasting
confidence: 77%
“…Due to the upward trend of this cancer mortality (Taghavi et al, 2012) and based on similar patterns, it is expected that the mortality rate in Iranian women population generally increase (Haghighat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Woman breast cancer is the most important cause of mortality in the world (Haghighat et al, 2012;Yang et al, 2012). The occurrence, development, and metastasis of breast cancer are closely associated with mutations in a variety of genes, alterations in cell signaling pathways, and neovascular dysplasia, all of which involve multiple critical steps (Huang et al, 2011;Connolly and Stearns, 2012).…”
Section: Discussionmentioning
confidence: 99%